THE PORTRAYAL OF CHARACTERS AND EDUCATIONAL VALUES IN “THE LAND OF FIVE TOWERS - Nur 'Amaliah; Rifari Baron (Universitas Indraprasta PGRI, 2021)
Abstract: The objective of the research is to know: 1) The characters in the novel